2021
DOI: 10.3390/ma14030698
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Material Properties of Mortar Reinforced with Glass Fiber: An Experimental Study

Abstract: The progressive increase in the amount of glass waste produced each year in the world made it necessary to start the search for new recycling methods. This work summarizes the experimental results of the study on mortar samples containing dispersed reinforcement in the form of glass fibers, fully made from melted glass waste (bottles). Mortar mixes were prepared according to a new, laboratory-calculated recipe containing glass fibers, granite as aggregate, polycarboxylate-based deflocculant and Portland cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 49 publications
5
24
0
Order By: Relevance
“…However, the concrete mixtures did not reach the melting temperature of any fiber material or even its softening temperature during the concrete production and later care, which could change the pH value. A similar trend was also reported by Małek et al [29], who tested the pH values of concrete mortars with fiber reinforcement and reported results in the range from 12.83 ± 0.03 to 12.97 ± 0.03.…”
Section: The Ph Testsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the concrete mixtures did not reach the melting temperature of any fiber material or even its softening temperature during the concrete production and later care, which could change the pH value. A similar trend was also reported by Małek et al [29], who tested the pH values of concrete mortars with fiber reinforcement and reported results in the range from 12.83 ± 0.03 to 12.97 ± 0.03.…”
Section: The Ph Testsupporting
confidence: 89%
“…Therefore, it can be concluded that the addition of fiber to the cement mix had no effect on the initial and final setting times. The same conclusion has been made by Małek et al [29,49], who reported no influence of glass and polypropylene fibers on the initial and final setting time of concrete mortars. The surfaces of PF, GF and SF are without roughness and smooth (Figure 4), therefore no agglomeration was observed during mixing.…”
Section: Initial and Final Setting Timesupporting
confidence: 84%
See 1 more Smart Citation
“…Waste and by-products from other industry branches can be re-used by the construction industry as a component of concrete and mortar [ 12 , 13 , 14 , 15 ]. According to current studies, they can be used as a replacement of natural aggregate [ 16 ] and cement [ 17 ], as dispersed reinforcement [ 18 , 19 , 20 , 21 ] to lower surface stress and prevent microcracks or as a filler to increase thermal properties of final composite [ 22 ]. Ferronickel slag waste has a potential to substitute natural aggregate as it is a solid discharged from the smelting process of metal nickel or nickel-iron alloy.…”
Section: Introductionmentioning
confidence: 99%
“…During the hardening stage for cement forming, cracks and voids are easily left in the structure [3]; these characteristics reduce the bearing capacity of the cement and accelerate the erosion effect of corrosive media, thus reducing the service life of the cement structure. Nowadays, the performance of cement has been improved by many efforts such as adjusting the cement mortars ratio, optimizing the aggregate gradation, and adding reinforcements [4][5][6][7]. However, these do not change the structure of cement hydration products, and the problems of high brittleness and cracking of the cement mortars still exist.…”
Section: Introductionmentioning
confidence: 99%